Evaluation Of The Level Of Usefulness Of The “Jeknyong” Application Using The Computer System Usability Questionnare (CSUQ) Method - Yohanna Sitorus; Sarah Astiti; Resad Setyadi (Journal of INISTA, 2023)
The Jeknyong application (Ojeke Inyong) is a household garbage collection service application with a transaction value. However, the use of the Jeknyong application has not been maximized because there are obstacles, such as several features still in development. This study discusses the Evaluation of the Level of Usability of the "Jeknyong" Application using the Computer System Usability Questionnaire (CSUQ) method, where Usability is a technique to find out how easily users can use the system, how efficiently and effectively the system can help users achieve goals. Data collection used a questionnaire with Banyumas community subjects who knew the Jeknyong application. The results are in the form of an indexed percentage of 85% in the Agree Interval category. The first variable System Usability (SYSUSE) evaluation results were 5135 or in the agreed interval. The second variable Information Quality (INFOQUAL) was 4588 or in the Fairly Disagree category. The third variable, Interface Quality (INTERQUAL), was 2039 or in the Agree category; the third variable, Overall Usability (OVERALL), gets a result of 709 or is in the Strongly Agree interval.